HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN TINGKAT KECEMASAN PADA LANSIA PENDERITA TBC DI WILAYAH PUSKESMAS KALIMULYA - Wanda Aranta Saski; Ns.Indri Sarwili; Nurul Ainul Shifa (SINERGI : Jurnal Riset Ilmiah, 2026)
Introduction: Family social support is a crucial factor in managing stress levels because it plays a crucial role in determining the behavior of sick family members. Chronic patients, particularly those with tuberculosis, often exhibit feelings of anxiety, frustration, irritability, and guilt. This study also aims to determine the relationship between social support and anxiety levels in elderly patients with pulmonary tuberculosis. Objective: The objective of this study was to determine the relationship between family social support and anxiety levels in elderly TB patients at the Kalimulya Depok Community Health Center. Method: This study used a cross- sectional approach. The population was all elderly patients with pulmonary TB. The sample used was 30 respondents using the Total Sampling Technique. This study was conducted in the Kalimulya Depok Community Health Center area. Results: From the Spearman Rank correlation test (rho), the calculated r value (0.585) was obtained > with a significance level of 0.05, so a positive correlation of 0.01 was obtained (p value <0.05) so that it can be stated that there is a significant relationship between family social support and anxiety levels of elderly TB patients. Conclusion: The higher the family social support provided, the lower the anxiety levels of elderly TB patients. Family social support provided by family members is very important in the healing process of elderly TB patients